Perception of Portuguese and Brazilian Dentists Regarding the Importance of Teeth and Dental Materials After Exposure to High Temperatures: Forensics Perspective - Beatriz Ramos; Isabel Abreu; Maria Teresa Moreira; Augusta Silveira; Inês Lopes Cardoso; Maria Inês Guimarães (Forensic Sciences)
Background: The main objective of this study was to carry out an online questionnaire in order to assess dentists’ knowledge and perception of dental materials submitted to high temperatures, helping to clarify and raise awareness of possible gaps in the area of forensic dentistry, especially in human identification. Results: Out of a total of 272 respondents, there was a greater influx of responses from countries such as Portugal and Brazil, the majority being female (66.3%), with an average age of 39 years. Most dentists consider complete clinical records to be extremely important. In addition, professionals with less experience provide fewer models in releasing their clinical records. In the case of dental materials, dentists consider composite resin and glass ionomers to be more susceptible to changes in shape and colour, while amalgam is considered the most stable, followed by ceramic and metal-ceramic crowns. On the other hand, dentin is considered more susceptible to colour changes than enamel. Enamel is seen by most professionals as resistant, undergoing few changes in shape at high temperatures. Conclusions: The opinion of the surveyed dentists on this subject is broadly in line with the existing literature. The only observed differences were related to exposure time and enamel resistance, since they assume that enamel is more resistant, and dentin is more vulnerable.